THE АТТITUDE OF THE MACEDONIAN ACADEMIC COMMUNITY TOWARDS THE “TORBESHI”: METHOD OF SOLIDARITY OR SCIENTIFIC SUBJECTIVITY? - Ana Ashtalkovska Gajtanoska (EtnoAntropoZum)
The title is inspired by the article of Lisa M. Tillman Healy, "Friendship as Method" (Tillmann-Healy, 2003), in which she advocates the ethics of friendship in her research. This method is appropriate, especially when dealing with sensitive and intimate research topics, and is based on the principles of interpretivism, feminist research, queer methodologies, activist research, etc., which oppose the myth of value-neutral research (Harding 1991, according to Tillmann-Healy, 2003: 733), the myth of universal truths and other positivistic principles.